SOAMANET: A Tool for Evaluating Service-Oriented Architectures on Mobile Ad-Hoc Networks - Neema, H; Kashyap, A; Kereskenyi, R; Yuan Xue; Karsai, G (2010 IEEE/ACM 14th International Symposium on Distributed Simulation and Real Time Applications, 2010)
Service-Oriented Architectures (SOAs) are increasingly being used for designing and building large-scale networked and distributed systems. Catering to the complex and dynamically varying needs of business applications/clients, these systems must usually be realized by dynamically composing a variety of network-available services. Evaluation of large-scale SOAs, particularly on dynamic network platforms, such as Mobile Ad-hoc Networks (MANETs), is a non-trivial problem that requires not only a correct modeling of SOAs and the network platform, but also their relationships. This paper describes a new tool - SOAMANET - to design and rapidly synthesize simulations for the experimental evaluation of SOAs on MANET platforms. With its modeling techniques and analysis capabilities, SOAMANET allows simulation-based and system execution-based analysis of dynamic SOA and/or MANET designs and implementations.